Towards registered single quantum dot photonic devices. - Lee, K; Brossard, F; Hadjipanayi, M; Xu, X; Waldermann, F; Green, A; Sharp, D; Turberfield, A; Williams, D; Taylor, R (2008)
We have registered the position and wavelength of a single InGaAs quantum dot using an innovative cryogenic laser lithography technique. This approach provides accurate marking of the location of self-organized dots and is particularly important for realizing any solid-state cavity quantum electrodynamics scheme where the overlap of the spectral and spatial characteristics of an emitter and a cavity is essential. We demonstrate progress in two key areas towards efficient single quantum dot photonic device implementation. Firstly, we show the registration and reacquisition of a single quantum dot with 50 and 150 nm accuracy, respectively. Secondly, we present data on the successful fabrication of a photonic crystal L3 cavity following the registration process.